Venular Basement Membranes Ubiquitously Express Matrix Protein Low-Expression Regions: Characterization in Multiple Tissues and Remodeling during Inflammation - Voisin, Mathieu-Benoît (American Society for Investigative Pathology, 2010)
The venular basement membrane plays a critical role in maintaining the integrity of blood vessels and through its dense and highly organized network of matrix proteins also acts as a formidable barrier to macromolecules and emigrating leukocytes. Leukocytes can however penetrate the venular basement membrane at sites of inflammation, though the associated in vivo mechanisms are poorly understood. Using whole mount immunostained tissues and confocal microscopy, we demonstrate that the venular basement membrane of multiple organs expresses regions of low matrix protein (laminin-511 and type IV collagen) deposition that have been termed low-expression regions (LERs). In the multiple tissues analyzed (eg, cremaster muscle, skin, mesenteric tissue), LERs were directly aligned with gaps between adjacent pericytes and were more prevalent in small venules. As predicted by their permissive nature, LERs acted as “gates” for transmigrating neutrophils in all inflammatory reactions investigated (elicited by leukotriene B(4) [LTB(4)], CXCL1, tumor necrosis factor [TNF]α, endotoxin, and ischemia/reperfusion [I/R] injury), and this response was associated with an enhancement of the size of laminin-511 and type IV collagen LERs. Transmigrated neutrophils stained positively for laminins but not type IV collagen, suggesting that different mechanisms exist in remodeling of different basement membrane networks. Collectively the findings provide further insight into characteristics of specialized regions within venular basement membranes that are preferentially used and remodeled by transmigrating neutrophils.